7 - Répartition personnelle des revenus, pauvreté et croissance économique en Côte d’Ivoire*: 10.4314/ad.v26i2.22146 - Bamba , Lambert N'galadjo (Africa Development, 2001)
This study explores the causality link between the state of income distribution and economic growth. The findings indicate that (i) an increase in poverty constitutes a brake in growth due to the weakening of the domestic market, while a reduction in poverty, through the increase in low incomes, allows an assured growth mostly by expanding domestic markets; (ii) the narrowing of inequalities encourages a potential growth due to the enlargement of domestic market by the circulation of new goods in society, whereas the increase in inequalities causes a potential growth provoked by the acquirement of new goods by the holders of surplus, and/or by exports. For this potential growth to become effective, the delays of maturation of new goods' markets should not be long. These findings are from empirical investigadon drawn from Côte d'Ivoire..